188k views
5 votes
to solve the system of equations below, grace isolated the variable y in the first equation and then substituted into the second equation. what was the resulting equation? 3y=12x x^2/4+y^2/9=1

User JahMyst
by
5.0k points

2 Answers

3 votes

Answer:


(x^2)/(4)+((4x)^2)/(9)=1

Explanation:

Given system of equations,


3y=12x-----(1)


(x^2)/(4)+(y^2)/(9)=1----(2)

As per statement,

Isolating the variable y in the first equation,


y=(12)/(3)x=4

Now, substituting into the second equation,


(x^2)/(4)+((4x)^2)/(9)=1

Which is the resulting equation,

Simplifying the equation,


(x^2)/(4)+(16x^2)/(9)=1


(9x^2+64x^2)/(36)=1


73x^2=36

User Pankaj Bansal
by
5.3k points
4 votes

Answer:

The resulting equation is

x^2/4+16x^2/9=1

Explanation:

The given equations are:

3y=12x eq(1)

x^2/4+y^2/9=1 eq(2)

We need to isolate variable y in equation 1

Divide both sides of the equation with 3

3y/3 = 12x/3

y = 4x

Now, substitute the value of y=4x in second equation

x^2/4+y^2/9=1

x^2/4 + (4x)^2/9 = 1

The resulting equation is

x^2/4+16x^2/9=1

User LikerRr
by
5.6k points